(untitled) (Revista Brasileira Multidisciplinar, 2026)
The work of Endemic Disease Control Agents involves raising awareness among the population through educational activities and implementing interventions to prevent and control arboviruses. The objective was to identify the challenges faced by Endemic Disease Control Agents in combating dengue fever in the municipality of Mato Verde, Minas Gerais. This is a descriptive, qualitative study conducted with 10 Endemic Disease Control Agents. Data were collected from August to September 2024 through semi-structured interviews and analyzed using Thematic Analysis. The results indicated that professionals recognize the importance of their role in the community in preventing the proliferation of Aedes Aegypti. The lack of awareness among the population and access to closed residences during home visits represent obstacles that prevent them from inspecting properties and raising awareness among residents about preventive measures. This limitation compromises the identification of mosquito breeding sites and increases the risk of proliferation of dengue fever and other diseases. The work exposes professionals to physical, chemical, biological and accident risks due to contact with larvicides, venomous animals and accumulated garbage, since the provision of protective equipment is not always adequate. This being said, it is clear that the work of Endemic Disease Control Agents is essential for promoting health and preventing diseases, so it is essential to continue to offer regular training so that professionals can stay up to date on best practices and improve their dengue control skills.